Slippage flow of second-grade fluid over a vertical plate with thermo-diffusion effect: an application of hybrid fractional operator - Shafique A.; Ramzan M.; Abbas S.; Shahryar M.; Nazar M.; Jan R.; Aljedani J.; Garalleh H.A.L. (Taylor and Francis Ltd., 2025)
This research investigates the effects of slip and thermo-diffusion on magnetohydrodynamic fluid flow and heat transfer through a porous medium, using a fractional second-grade fluid model. A semi-analytical solution is obtained through Laplace transform techniques, revealing detailed insights into concentration, temperature, and velocity distributions. The study sheds light on the significant impact of key parameters, including Prandtl and Schmidt numbers, Grashof numbers, and the second-grade parameter, on the intricate relationships between thermo-diffusion, slip conditions, and fluid flow in porous media. ? 2024 Informa UK Limited, trading as Taylor & Francis Group.